Pendidikan Al-Qur’an Sebagai Upaya Pelaksanaan TPQ di Desa Ngemplak Seneng - Ajeng Nabila; Zaki Afifi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Taman Pendidikan Al-Qur’an (TPQ) functions as a non-formal Islamic educational institution that is very important in fostering Al-Qur’an literacy among Muslim children, especially in rural areas that have limited access to formal religious education. This study aims to examine the implementation of the Al-Qur’an education program at TPQ An-Nur, Ngemplak Seneng Village, Manisrenggo District, Klaten Regency, based on the framework of five core programs: reading, writing, memorizing, understanding the meaning of the Al-Qur’an, and moral character education. Using a descriptive-qualitative approach through direct observation, interviews, and documentation, the findings show that although the five programs have been implemented, their overall implementation is still not optimal. Only 32% of students are able to read directly from the mushaf, memorization targets do not have structured periodic benchmarks, and both Al-Qur’an understanding and moral education are delivered situationally without consistent planning. This study contributes as a reference for TPQ managers and stakeholders who seek to improve the quality of Al-Qur’an learning programs in rural communities with limited resources. Further research is recommended to evaluate the effectiveness of each program more deeply in order to support the sustainable quality improvement of rural TPQ.